Small palladium clusters and their adducts with atomic oxygen. (15th November 2022) - Lysova, Anna A.; Benassi, Enrico; Matveev, Andrey V.
Graphical abstract: A joint computational-experimental study on Pd clusters and on the early stages of the oxygen-cluster interaction. Abstract: A systematic investigation on small Pd n clusters ( n  = 1 ÷ 8) and their interaction with atomic oxygen was conducted at DFT level. A model to describe cohesive energy for small sized clusters based on a topological approach was proposed and validated. On the basis of the bond length, the stabilisation electronic energy and the second electronic energy difference variation analysis, Pd4 and Pd6 were identified as the most stable clusters. The Natural Bond Orbital (NBO) analysis and the plot of the Molecular Electrostatic Potential (MEP) – both performed for the first time – indicated that the Pd atoms in clusters were not equivalent in terms of atomic charge, population and electron configuration. The plots of the MEP mapped on the electron density also revealed its non-uniform character; areas of positive MEP were found around the Pd atoms, which may undertake nucleophilic attacks. Subsequently, the interaction of atomic oxygen with Pd n clusters was systematically studied, accounting for different possible anchoring positions. The hollow site was revealed to be the most favourable one. The increase in number of Pd atoms favoured higher spin states. Pd6 O was identified as the most oxidised and energetically stable cluster. The calculated binding energy value of oxygen (3.5 eV) was in agreement with the Temperature Programmed Desorption (TPD) experimental results conducted on Pd(1 1 0) single-crystal surface. The NBO analysis evidenced that the occupancy of 2  s (2 p ) orbital of O decreased (increased) as the number of Pd atom increased. The negatively charged Pd atoms had a larger population of 4 d orbitals than the neutral or positively charged ones. The interactions between O and Pd atoms were dominated by d -type orbitals.